1994
DOI: 10.1038/368455a0
|View full text |Cite
|
Sign up to set email alerts
|

High resolution of human evolutionary trees with polymorphic microsatellites

Abstract: Genetic variation at hypervariable loci is being used extensively for linkage analysis and individual identification, and may be useful for inter-population studies. Here we show that polymorphic microsatellites (primarily CA repeats) allow trees of human individuals to be constructed that reflect their geographic origin with remarkable accuracy. This is achieved by the analysis of a large number of loci for each individual, in spite of the small variations in allele frequencies existing between populations. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

69
1,247
8
16

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,660 publications
(1,340 citation statements)
references
References 19 publications
69
1,247
8
16
Order By: Relevance
“…However, the diversity within the Indian populations, represented by the long branches and links connecting many haplotypes, is also an indicator of their ancestry, geographical differentiation and severe bottlenecks within India, suggesting loss of many of the intermediate haplotypes, thus reducing the reticulation and increasing the branches' length. The observed genetic distances FST 38 and 1ÀPSA 44 within the R1a1* haplogroup, between Central Asians (CA), Europeans (EU), as well as pooled populations of the Indian subcontinent (IS) showed overlapping trends of distribution. FST is based on the total variance in allele frequencies among populations and 1ÀPSA considers shared allele frequencies.…”
Section: Nested Cladistic Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…However, the diversity within the Indian populations, represented by the long branches and links connecting many haplotypes, is also an indicator of their ancestry, geographical differentiation and severe bottlenecks within India, suggesting loss of many of the intermediate haplotypes, thus reducing the reticulation and increasing the branches' length. The observed genetic distances FST 38 and 1ÀPSA 44 within the R1a1* haplogroup, between Central Asians (CA), Europeans (EU), as well as pooled populations of the Indian subcontinent (IS) showed overlapping trends of distribution. FST is based on the total variance in allele frequencies among populations and 1ÀPSA considers shared allele frequencies.…”
Section: Nested Cladistic Analysismentioning
confidence: 98%
“…44 The spatial frequency/diversity maps were generated by the Kriging procedure 45 using SURFER version 8.0 (Golden Software Inc., CO, USA). Spearman's rank correlation coefficient, which has values +1 and À1 for perfect positive and negative correlations, respectively, 46 was calculated for the latitude and longitude with haplogroup frequency and diversity by applying the formula in Microsoft Excel.…”
Section: Statistical and Phylogenetic Analysesmentioning
confidence: 99%
“…Many clustering algorithms have been developed employing population genetic data to assign individuals to clusters (Jakobsson and Rosenberg, 2007). Several statistical methods were used to determine which genetic markers contain the most information to discriminate among populations (Rosenberg, 2005;Wilkinson et al, 2011), such as the combined approach of principal component analysis (PCA) and random forest (RF) (Bertolini et al, 2015), multivariate canonical discriminant analysis (Dimauro et al, 2013), the statistic delta (Shriver et al, 1997), and Wright's F st (Bowcock et al, 1994). While all these methodologies yielded reduced marker panels useful for breed identification, the power of assignment varied among analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…We quantified microsatellite genetic diversity using mean number of alleles ( A ), observed heterozygosity ( H O ), and expected heterozygosity ( H E ) over all loci, using program GenAlEx (v. 6.0, Peakall & Smouse, 2006). We estimated inter‐individual GD, by calculating the ratio proportion of shared alleles (Dps, GD = (1 − Dps); Bowcock et al., 1994) for each pairwise combination of individuals using GenAlEx v. 6.0 (Peakall & Smouse, 2006). Dps is a commonly used individual‐based genetic distance measure in landscape genetic studies and has been shown to accurately reflect SGS and connectivity at small spatial scales (Murphy, Dezzani, Pilliod, & Storfer, 2010).…”
Section: Methodsmentioning
confidence: 99%